2016
DOI: 10.1093/jnci/djw148
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms of Therapy Resistance in Patient-Derived Xenograft Models of BRCA1-Deficient Breast Cancer

Abstract: In addition to previously described clinically relevant resistance mechanisms in BRCA1-deficient tumors, we describe a novel resistance mechanism in BRCA1-methylated PDX tumors involving de novo rearrangements at the BRCA1 locus, demonstrating that BRCA1-methylated breast cancers may acquire therapy resistance via both epigenetic and genetic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
149
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 43 publications
9
149
0
1
Order By: Relevance
“…A potential limitation of these approaches is the lack of specificity in HRR‐altered tumors that have restored the HRR function (Watkins et al , ; Konstantinopoulos et al , ). Other approaches entail the quantification of BRCA1 promoter hypermethylation, BRCA1 mRNA expression, or the detection of the HRR protein RAD51 forming nuclear foci after DNA damage, as surrogate of HRR functionality (Graeser et al , ; Naipal et al , ; ter Brugge et al , ). In these sense, we showed that, in gBRCA tumors, RAD51 foci could be detected in untreated samples and correlated with PARPi resistance regardless of the underlying mechanism restoring HRR function (Cruz et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…A potential limitation of these approaches is the lack of specificity in HRR‐altered tumors that have restored the HRR function (Watkins et al , ; Konstantinopoulos et al , ). Other approaches entail the quantification of BRCA1 promoter hypermethylation, BRCA1 mRNA expression, or the detection of the HRR protein RAD51 forming nuclear foci after DNA damage, as surrogate of HRR functionality (Graeser et al , ; Naipal et al , ; ter Brugge et al , ). In these sense, we showed that, in gBRCA tumors, RAD51 foci could be detected in untreated samples and correlated with PARPi resistance regardless of the underlying mechanism restoring HRR function (Cruz et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that PDXs retain the genome-wide exomic nucleotide variants, gene copy number alterations, and DNA methylation patterns of their corresponding tumors [1][2][3][4] irrespective of the number of passages, 1,3 although clonal selection during initial engraftment and passaging of PDXs has been observed. 4 PDX models also are increasingly used in the mechanistic characterization of resistance to targeted therapies, [9][10][11] the identification of novel Cancer November 1, 2019 biomarkers 12 and therapeutic targets, 13 and the characterization of intratumoral heterogeneity. 7,8 An analysis of the treatment responses of PDXs established from 92 patients with different solid tumors demonstrated a significant association between drug response in patients and the response in mice bearing the corresponding PDXs, indicating that PDXs can predict clinical treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…In an in vitro setting it was found that BRCA1 promoter methylation in the wild-type UACC3199 breast cancer cell line was equally sensitive to PARP inhibition as the BRCA1 mutant MDA-MB-436 line (49). In addition, a patient-derived xenograft model confirmed the presence of BRCA1 methylation in a subset of tumors, and that loss of methylation was associated with PARP inhibitor resistance in this context (50). These data hint at a possible epigenetic role in determining likely sensitivity to PARP inhibitors that could be used in treating patients with breast or ovarian cancer.…”
Section: Epigenetic Predictive Biomarkersmentioning
confidence: 86%